EVALUATION OF MORPHOLOGICAL AND PHYSIO-CHEMICAL CHANGES IN PHYTOPLASMA INFECTED BRASSICA NAPUS - S. Yaseen; S. Tanwir; J. N. Ahmad; M. Hussain; Z. Aslam (Journal of Animal and Plant Sciences, 2020)
Phytoplasmas are bacterial plant pathogens associated with various diseases causing yield losses in agricultural production worldwide. Symptoms of phytoplasma include small leaf size, stunted growth and malformation of floral leaves. Infected plants show a number of biochemical changes and activation of antioxidant enzymes to defend themselves from the plant pathogen. The objective of current experiment was to investigate the morphological and Physio-chemical changes induced in phytoplasma infected leaves of Brassica napus plants. Healthy Brassica napus plants were exposed to infection through the insect vector Orosious orientalis after which leaves from a set of healthy and inoculated plants were employed to analyze and compare their antioxidative enzyme activity and other defense related compounds. The data revealed that phytoplasma attack resulted in small leaf size and stunted growth along with malformation of flowers. Such plants showed lower chlorophyll a, b and total chlorophyll but higher level of phenolics, amino acids, free proteins and H2O2 contents as compared to the healthy plants.
Keywords: Phytoplasma; Orosious orientalis; Brassica napus; superoxide dismutase; phenolics; flower morphology